ROAD SAFETY IN THE REPUBLIC OF SERBIA - Herber, Franz-Rudolf (European Scientific Journal, ESJ, 2015)
The term “road safety" is an Anglicism, that is incorporated in the German language and many other languages of the world; any translation of "road safety" may not have the mythical effect that emanates from the English term. Road safety is a global issue, road users do expect that in all states of the world efforts are undertaken in order to ensure a high level of safety for road users. It is therefore not surprising that global organizations are committed to road safety. This applies particularly to the World Health Organization (WHO) as a body of the United Nations (UN) and the Organization of the Organization for European Economic Cooperation (OECD). The WHO presented in its >Global Status Report on Road Safety 2013< important results referring to road safety in 182 countries and thus covers 99% of the world population54. The WHO did grant Serbia in the year 2013 the sum of US 100 million for the improvement of road infrastructure and road safety.